Analysis of Stiffening Methods and Effects on Irregular Single-layer Lattice Shell Structures - Jianshe Xu (Journal of Engineering and Technological Sciences, 2018)
Local stiffening is often a good solution to mechanical property problems of irregular single-layer lattice shell structures. The effects of three local stiffening methods, namely section enlargement stiffening, planar truss stiffening, and space truss stiffening, on their structural stiffness, strength, and overall stability were analyzed in this study. A practical engineering example showed that these three stiffening methods could effectively reduce the deformation of the lattice shell under vertical and lateral loads, reduce the comprehensive stress ratio, and increase the buckling eigenvalue and ultimate bearing capacity factor. The local space truss stiffening method had the best comprehensive effect. The same stiffening methods were applied to a regular lattice shell and the analysis showed that the stiffening effect on a regular shell is quite different from that on an irregular lattice shell. The three stiffening methods could not reduce its deformation under vertical loading but could reinforce the strength and overall stability of the structure effectively. Proper suggestions are proposed according to the preceding analysis in case a single-layer lattice shell structure cannot meet the demands of the design code.